Adult Attachment and Self Esteem - Yahya, Fatahyah; Nurshafiqah Azhar, Anis; ., . (International Journal of Engineering and Technology, 2018)
This study identifies the relationship between adult attachment, and specifically between attachment avoidance, attachment anxiety and self-esteem among married couples residing in the north-east of Peninsular Malaysia. A correlational research design was adopted to address the research objectives established for this study involving a representative sample of seventy married couples from the north-east of Peninsular Malaysia. Two sets of questionnaires were developed and reviewed by two expert panels before piloting and finalising. The structure and content of the questionnaires were specific to main two areas; Experience in a Close Relationship (ECR) scale and Rosenbergâ€™s Self-Esteem Scale (RSE). The questionnaires were then distributed to the participants. The data were collected and analysed using descriptive statistical analysis and Pearson Correlation. The findings indicated the existence of a meaningful relationship between adult attachment and self-esteem. Furthermore, it was recommended based on the work performed, limitations and findings that further research is conducted in a similar program, but a with broader and a more substantial population size covering multiple communities, again with a specific focus on married couples and improving their attachment and self-esteem in a relationship.Â Â Â